PERKEMBANGAN NILAI-NILAI KARAKTER DALAM PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SMK PGRI ENREKANG - Ratna Ratna; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
This study aims to describe the development of character values ​in learning Pancasila and Citizenship Education which includes planning, implementation, assessment, and obstacles or obstacles faced as well as solutions sought in the learning that takes place at SMK PGRI Enrekang. This type of research is a qualitative research with a case study research design. Implementation of research at SMK PGRI Enrekang. Data collection techniques carried out by the method of interviews (interviews), observation and documentation. The data analysis technique uses interactive model of analysis, while the data validity analysis method uses source triangulation. The results of this study are the inculcation of character values ​​in learning Pancasila and Citizenship Education at carried out by preparing a lesson plan in the form of lesson plans that include character values ​​to be achieved, preparing media and learning resources, carrying out an interactive learning process, conducting an assessment/evaluation. which includes, assessment of attitudes (affective) using an attitude scale which is carried out through the teaching and learning process in the classroom and outside the classroom in extra-curricular or other activities in the form of habituation at SMK PGRI Enrekang, while the assessment of knowledge (cognitive) is carried out through repetition